2013
DOI: 10.1016/j.cryobiol.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Temperature fluctuations during deep temperature cryopreservation reduce PBMC recovery, viability and T-cell function

Abstract: The ability to analyze cryopreserved peripheral blood mononuclear cell (PBMC) from biobanks for antigen-specific immunity is necessary to evaluate response to immune-based therapies. To ensure comparable assay results, collaborative research in multicenter trials needs reliable and reproducible cryopreservation that maintains cell viability and functionality. A standardized cryopreservation procedure is comprised of not only sample collection, preparation and freezing but also low temperature storage in liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 52 publications
2
58
0
Order By: Relevance
“…2A), confirming the effect of the process on cellular viability. The median (range) of nonviable PBMCs from healthy children was low (4.6% [1% to 19%]) after cryopreservation and comparable to that reported previously (5,23), demonstrating the efficiency of the freezing protocol used here ( Fig. 2A).…”
Section: Resultssupporting
confidence: 58%
“…2A), confirming the effect of the process on cellular viability. The median (range) of nonviable PBMCs from healthy children was low (4.6% [1% to 19%]) after cryopreservation and comparable to that reported previously (5,23), demonstrating the efficiency of the freezing protocol used here ( Fig. 2A).…”
Section: Resultssupporting
confidence: 58%
“…9,[15][16][17] Although, as expected, fluctuating temperatures experienced by the cells in transit resulted in a lower yield of viable cells, antigen-specific B MEM frequencies could still be reliably measured. Compared with T cells, which have been shown to display reduced antigen-specific responses after experiencing fluctuating storage temperatures, 18 B MEM may be more resilient under these conditions. Although previous studies have shown that low cell viability following cryopreservation can compromise lymphocyte proliferation in response to mitogens including PWM, 33 the present study shows that after allowing for lower viable cell numbers following storage and shipment, freezing of PBMC did not affect the numbers of viable PBMCs that were harvested after a 6-d culture compared with fresh samples.…”
Section: Discussionmentioning
confidence: 99%
“…29 The maintenance of T cell functionality during cryopreservation is therefore very important to produce reliable results. 10,26,30–34 …”
Section: Introductionmentioning
confidence: 99%